Sex, crime and literature in Victorian England - Ward, Ian (Hart, 2014)
An exploration of the texts which shaped Victorian attitudes towards the 'condition' of England and the 'question' of its women. It offers a richly contextual commentary on a critical period in the evolution of modern legal and cultural attitudes to the relation of crime, sexuality and the family